Oxidative DNA damage is instrumental in hyperreplication stress-induced inviability of Escherichia coli - Charbon, Godefroid (Nucleic Acids Res, 2014)
In Escherichia coli, an increase in the ATP bound form of the DnaA initiator protein results in hyperinitiation and inviability. Here, we show that such replication stress is tolerated during anaerobic growth. In hyperinitiating cells, a shift from anaerobic to aerobic growth resulted in appearance of fragmented chromosomes and a decrease in terminus concentration, leading to a dramatic increase in ori/ter ratio and cessation of cell growth. Aerobic viability was restored by reducing the level of reactive oxygen species (ROS) or by deleting mutM (Fpg glycosylase). The double-strand breaks observed in hyperinitiating cells therefore results from replication forks encountering single-stranded DNA lesions generated while removing oxidized bases, primarily 8-oxoG, from the DNA. We conclude that there is a delicate balance between chromosome replication and ROS inflicted DNA damage so the number of replication forks can only increase when ROS formation is reduced or when the pertinent repair is compromised.